Pengembangan Karakter Guru Melalui Keterampilan Menulis Artikel - Rusdiono Mukri; A. Abbas Arby (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2022)
The community service activities aim to develop a strengthen of character education for school teachers of Early Childhood Education (ECE) and Ibtidaiyah Madrasa (MI) at the Pamijahan district. The character development of the teachers is expected to be the writer of journal local articles, and the symbols of change of the participants.To achieve these goals, community service activities use empowerment methods for partner community training â€œsarasehanâ€, which are carried out in a sustainable manner. The community service activities refer to the education policy regulated in Law Number 20 of 2003, and Presidential Regulation Number 87 of 2017 concerning the strengthening of character in the education system. The strengthening of character education is a main program to foster strong character in participants through harmonization of thought, literacy, etic, and kinesthetic of â€œwritten skillâ€. By strengthening character education in this participantâ€™s activity, it becomes a program to elevate optimal character potential for the participants. The target of community service activities is to involve around 30 participating teachers from the Pamijahan district. The implementation output of community service activities is an action plan for 4 (four) months, making workshop material modules, and the skill of writing at a local journal articles.